Fire bound ebook - Feehan, Christine (Sea Haven: Sisters of the Heart, 2016)
A woman possesses the power to inflame the most dangerous passions of all in this Sisters of the Heart novel from #1 New York Times bestselling author Christine Feehan. On the shores of Sea Haven, six women touched by great loss have come together in a sisterhood strengthened by the elements—a bond each will need as new love and danger enter their lives... Flame-haired Lissa Piner is a skilled glass blower whose delicate gift conceals a burning inner strength that can destroy as exquisitely as it can create. Commissioned to design chandeliers for a string of luxury hotels, her remarkable skills have taken her to Italy. But Lissa’s real mission there is a secret. For her entire life has been a lie, leading to a chance to avenge a terrible wrong. Enlisted as her bodyguard is Casmir Prakenskii, a trained assassin living off the grid. In Lissa, he sees a kindred spirit—something unexpected and wicked, mysterious and sensual. But more than desire is about to bring them together: because both of their pasts cry out for revenge. And for two people with this many secrets, this much passion, and this many enemies, someone is bound to get burned.